Study of the preparation of Cu2O/CPAN/SiO2 composite material and its photocatalytic reduction performance - Peng WANG (Hebei University of Science and Technology, 2021)
With porous SiO2 withhigh specific surface area as the carrier,Cu2O and CPAN with matching valence band as the catalysts,Cu2O/CPAN/SiO2 (cuprous oxide/cyclized polyacrylonitrile/silicon dioxide) composite photocatalyst was prepared by solution impregnation and in situ thermal decompositionin order to improve the specific surface area and electron-hole separation efficiency of the material.The morphology,composition and structure of the composite were characterized by TEM,SEM,XRD,FTIR,BET and EDS,and the photoelectric properties of the composite particles were analyzed by UV-VIS,DRS,PL,EIS and photocurrent methods.The visible light photocatalytic properties of Cu2O/CPAN/SiO2 composite particles were investigated in the model of the [WTBX]p[WTBZ]-nitrophenol reduction.The results show that porous SiO2 carrier greatly increased the specific surface area of Cu2O/CPAN.The Cu2O in octahedral crystal and the heterojunctions of CPAN are evenly distributed on the surface of SiO2 and significantly improve the absorption of visible light and the separation efficiency of photogenerated electron-hole pairs.When the content of Cu2O is 2%,the heat treatment temperature is 260 ℃,and the heat treatment time is 3 h,the prepared Cu2O/CPAN/SiO2composite particles exhibit the best photocatalytic activity.The results provide a method basis for preparing a high-efficiency composite catalyst.